2021
DOI: 10.1007/s00464-021-08596-7
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine green (ICG) fluorescent cholangiography during laparoscopic cholecystectomy using RUBINA™ technology: preliminary experience in two pediatric surgery centers

Abstract: Background Recently, we reported the feasibility of indocyanine green (ICG) near-infrared fluorescence (NIRF) imaging to identify extrahepatic biliary anatomy during laparoscopic cholecystectomy (LC) in pediatric patients. This paper aimed to describe the use of a new technology, RUBINA™, to perform intra-operative ICG fluorescent cholangiography (FC) in pediatric LC. Methods During the last year, ICG-FC was performed during LC using the new technology RUB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Multiple preliminary experiences have shown the safety and usefulness of ICG-FA in pediatric abdominal surgeries including minimally invasive surgeries (22,26), laparoscopic Palomo varicocelectomies (24), laparoscopic cholecystectomies (89), and laparoscopic partial nephrectomies (90). Currently, efforts are being made to standardize the technique and prove the benefits of the ICG-FA technology (89,90). A study published after the updated search of this review suggested a dose of 0.35 mg/kg of indocyanine green, 16-18 h before performing a laparoscopic cholecystectomy (89).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple preliminary experiences have shown the safety and usefulness of ICG-FA in pediatric abdominal surgeries including minimally invasive surgeries (22,26), laparoscopic Palomo varicocelectomies (24), laparoscopic cholecystectomies (89), and laparoscopic partial nephrectomies (90). Currently, efforts are being made to standardize the technique and prove the benefits of the ICG-FA technology (89,90). A study published after the updated search of this review suggested a dose of 0.35 mg/kg of indocyanine green, 16-18 h before performing a laparoscopic cholecystectomy (89).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, efforts are being made to standardize the technique and prove the benefits of the ICG-FA technology (89,90). A study published after the updated search of this review suggested a dose of 0.35 mg/kg of indocyanine green, 16-18 h before performing a laparoscopic cholecystectomy (89). The authors reported a 17% technical failure of intra-operative ICG fluorescence visualization (n = 2).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the intensity-map mode displays the ICG-NIRF signal intensity by changing the color according to the image type. 5 ) We used the overlay mode in this hematoma removal study. We performed ICG angiography using one ICG endoscope per case and compared the intraoperative findings.…”
Section: Case Reportmentioning
confidence: 99%
“…The bleeding points are challenging to identify, and postoperative bleeding has been reported as a serious complication after endoscopic hematoma removal. 5 ) Therefore, we performed intraoperative ICG near-infrared fluorescence (ICG-NIRF) imaging to locate the bleeding point and identify the damaged vessel causing the hemorrhage. The purpose of the study was to evaluate the usefulness of ICG angiography during endoscopic hematoma removal.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, clinical trials have explored numerous uses that might be particular to individual devices, some of them being encompassed within 510(k) indications of use. For example, in gallbladder removal surgery (laparoscopic cholecystectomy) the RUBINA™ guided surgery system combined with an ICG contrast agent has helped to identify biliary and vascular tissues, as well as the presence of abnormalities that can cause complications during surgery 13 …”
Section: Overview Of Open-field Fgs Contrasts Components and Parametersmentioning
confidence: 99%